Parent-Adolescent Agreement on Adolescents' Emotional and Behavioral Problems Assessed by the Strengths and Difficulties Questionnaire - Kentaro Kawabe MD, PhD; Fumie Horiuchi MD, PhD; Hiroyuki Uno PhD; Kiwamu Nakachi MD; Rie Hosokawa MD; Yasunori Oka MD, PhD; Shu-Ichi Ueno MD, PhD (SAGE Publishing, 2021)
Objective . The perception of emotion and behavior is different between adolescents and their parents. Parent-adolescent agreement on emotional and behavioral problems has not been well researched. The aim of this study was to explore and compare how well the information from themselves matches with the judgments by their parents in terms of emotional and behavioral problems. Methods . The cross-sectional study was conducted using the self-report and parent-report Strengths and Difficulties Questionnaire (SDQ). A total of 1254 Japanese school adolescents aged 12 to 18 and their parents were assessed almost the same time. The results were analyzed using the paired t -test and 2-way analysis of variance for the discrepancies of parent-adolescent agreements in each age and gender groups. Results . Adolescents obtained higher total difficulty and all subscales scores of SDQ than their parents. The effect of grade on the self/parent discrepancy scores were significantly observed on the conduct problems ( P  < .001), hyperactivity ( P  = .009), and prosocial behavior ( P  < .001). The effect of gender was shown significantly on the emotional problems ( P  < .001), conduct problems ( P  < .001), and peer problems ( P  = .002). Conclusion . Adolescents reported more problems than their parents did. For comprehensive evaluation of adolescents' mental health, it is necessary to draw information from both the adolescents themselves and their parents, and pay attention to the gap between adolescents and their parents' perception.